Mechanical properties of high impact Abs/Pc blends - effect of blend ratio - Hassan, Azman; Wong, Yean Jwu (2005)
Polymer blends are capable of providing materials which extend the useful properties beyond the range that can be obtained from single polymer equivalents. Blends of Acrylonitrile-Butadiene- Styrene (ABS) and Polycarbonate (PC) were prepared in different ratios by melt blending technique which was carried out using a twin screw extruder. A super high impact ABS at different weight ratios was incorporated into the blends to study the effects of blend ratio on the properties of the blend. This study focused upon tensile, flexural, impact and creep properties of ABS/PC blends. PC offered an improvement in tensile properties for this blend. With the increasing content of PC in ABS/PC blends, both the tensile strength and Young’s Modulus of the blends were increased. Both the flexural strength and modulus show a marked increase with increasing PC content. In general, impact strength increases with increasing PC content. However, sudden drop in the impact strength value occurred when small amount of PC (20 wt%) was added to the blends. The creep resistance of neat PC exhibited the highest value while neat ABS has the lowest value. The optimum formulation for the ABS/PC blends based on the mechanical properties and cost is 40: 60 ABS/PC blend ratio.